2016
DOI: 10.1002/adfm.201505502
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enhancement of Inner Tube Photoluminescence in Filled Double‐Walled Carbon Nanotubes

Abstract: A highly selective enhancement of the optical response of the inner tubes of double‐walled carbon nanotubes has been identified upon transformation of the residual C atoms inside the hollow core to linear carbon chains (LCC). By varying the growth conditions and using standardized suspensions, it has been observed that this optical response depends sensitively on the tube diameter and LCC growth yield. It is reported how the formation of LCC by postsynthesis annealing at 1400 °C leads to an increase of the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
(95 reference statements)
0
18
0
Order By: Relevance
“…Regarding the second effect, the observation of a rather strong electronic Raman scattering signal and broad component in the G band in the (14,1)@(15,12) DWNT [36] indicates that the doping level of this tube is, at most, of the order of 0.001 charge/atom [49,50]. Even if we cannot evaluate more precisely this doping, a recent study on DWNTs filled by linear carbon chains [27] has shown that balancing the intrinsic charge transfer between the outer tube and ISCT leads to a maximum increase of one order of magnitude of the PL signal. We thus infer that the main source of quenching would be the decay of the exciton through the lower-energy states of the outer tube compared to S i 11 [25].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Regarding the second effect, the observation of a rather strong electronic Raman scattering signal and broad component in the G band in the (14,1)@(15,12) DWNT [36] indicates that the doping level of this tube is, at most, of the order of 0.001 charge/atom [49,50]. Even if we cannot evaluate more precisely this doping, a recent study on DWNTs filled by linear carbon chains [27] has shown that balancing the intrinsic charge transfer between the outer tube and ISCT leads to a maximum increase of one order of magnitude of the PL signal. We thus infer that the main source of quenching would be the decay of the exciton through the lower-energy states of the outer tube compared to S i 11 [25].…”
Section: Discussionmentioning
confidence: 95%
“…[20]. This weak QY can be understood in terms of (i) ultrafast exciton transfer from the inner to outer tube as suggested by femtosecond time-resolved luminescence measurements [21] and time-domain ab initio simulations [25] and (ii) charge transfer from outer to inner tubes [26,27]. Regarding the second effect, the observation of a rather strong electronic Raman scattering signal and broad component in the G band in the (14,1)@(15,12) DWNT [36] indicates that the doping level of this tube is, at most, of the order of 0.001 charge/atom [49,50].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has enabled the study of pressure, charge transfer, and screening e↵ects on the chains and their nanotubes hosts, and revealed that the chirality of the encasing nanotube determines the BLA and hence the band gap and the C-mode frequency of the encapsulated LLCC [10,11,12,6]. The importance of Raman spectroscopy in characterising confined LLCCs is highlighted by the fact that the carbon nanotube hosts prohibit alternative direct optical methods such as absorption or photoluminescence spectroscopy by spectral overlap or quenching, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Note that we cannot recognize the contributions of the LCCs from the SWCNTs in this spectrum, since the weak absorption of LCCs overlapps and completely covered by the strong absorption of the SWCNTs. 31,32 The chirality assignment from the absorption shows that most of extracted tubes in the top layer are very small SWCNTs with diameters between 0.6 and 0.8 nm, 33 which are originally extracted from the inner tubes of DWCNTs. Furthermore, the Raman spectra shown in Fig.1c illustrate the difference between the two separated parts and confirm the successful extraction again.…”
Section: Resultsmentioning
confidence: 99%